Nilai Moral Pertunjukan Barongan Risang Guntur Seto Blora (Universitas Negeri Semarang, 2017)
Barongan Risang Guntur Seto in his show contains certain moral values. This study examines the moral values ​​that are showed in Barongan Risang Guntur Seto perfomance. The method used a qualitative approach with normative ethics. Collecting data through observation, interviews and documentation. Data analysis uses dance analysis based on Adshead Theory. The research results of the moral value Barongan Risang Guntur Seto is focussed on the theme, storyline, and accompaniment. Pattern sequence or structure of the performance is the opening, content/core and closing. The permance tell the responsibilities of soldiers on the king on the theme. Dramatic Geger Kediri storyline is about two knights who hold trust, namely Gembong Amijoyo and Jaka Lodra. Gembong Amijoyo has responsible to look after Alas Jati Wengker While Jaka Lodra gain the responsible of Panji Asmara Bangun to propose Dewi Sekartaji. Accompanying used in Barongan Risang Guntur Seto is Barongan Blora accompaniment depicting two knights of the character Gembong Amijoyo and Jaka Lodra in implementing Responsible. The moral values ​​of the Barongan Risang Guntur Seto performance is the kindness that is formed from religious, honest, tolerant, friendly, and responsibility while the disadvantage is the dispute between the brothers, which resulted in a fierce battle.